A Grammatical Cohesive Analysis In “English Students Learning Activities” Textbook for VIII Grade - Fitri, Ardellia Ananda Eka; Hayu Dian Yulistianti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates grammatical cohesive devices in textbook reading passages. Drawing on established cohesion theory by (M.A.K and Hasan 1975), the researcher analyzed dialogues, recount texts, and descriptive texts contained in the book by using a descriptive qualitative methodology. The findings revealed 281 distinct cohesive devices across four categories: references (190), conjunctions (85), substitution (4), and ellipsis (2), with reference being the most dominant. While the passages demonstrated coherence and accessibility, the limited variety of cohesive devices and vocabulary constrains their effectiveness as tools for cultivating critical thinking skills among students. This research highlights the relationship between textual cohesion and pedagogical effectiveness in educational materials designed to foster higher-order thinking.